Importance of Mitochondria in Cardiac Pathologies: Focus on Uncoupling Proteins and Monoamine Oxidases - Schulz, Rainer; Schlüter, Klaus-Dieter; Justus Liebig University Giessen (My University, 2023)
On the one hand, reactive oxygen species (ROS) are involved in the onset and progression of a wide array of diseases. On the other hand, these are a part of signaling pathways related to cell metabolism, growth and survival. While ROS are produced at various cellular sites, in cardiomyocytes the largest amount of ROS is generated by mitochondria. Apart from the electron transport chain and various other proteins, uncoupling protein (UCP) and monoamine oxidases (MAO) have been proposed to modify mitochondrial ROS formation. Here, we review the recent information on UCP and MAO in cardiac injuries induced by ischemia-reperfusion (I/R) as well as protection from I/R and heart failure secondary to I/R injury or pressure overload. The current data in the literature suggest that I/R will preferentially upregulate UCP2 in cardiac tissue but not UCP3. Studies addressing the consequences of such induction are currently inconclusive because the precise function of UCP2 in cardiac tissue is not well understood, and tissue- and species-specific aspects complicate the situation. In general, UCP2 may reduce oxidative stress by mild uncoupling and both UCP2 and UCP3 affect substrate utilization in cardiac tissue, thereby modifying post-ischemic remodeling. MAOs are important for the physiological regulation of substrate concentrations. Upon increased expression and or activity of MAOs, however, the increased production of ROS and reactive aldehydes contribute to cardiac alterations such as hypertrophy, inflammation, irreversible cardiomyocyte injury, and failure.
Keywords: ischemia; reperfusion; heart failure; pulmonary hypertension; reactive oxygen species; ddc:610